Pembelajaran Bahasa Sastra Melalui Pemberdayaan Kompetensi Guru - Nikmatul Izah (Universitas Yudharta Pasuruan, 2019)
Language has a central role in students' intellectual, social and emotional development. Languages ​​support students' success in learning all fields of study. Therefore, language learning must be interesting and fun for students. Indonesian language and literature learning in some schools is still not in accordance with what is expected. Teachers tend to use theoretical learning techniques so learning is rigid and boring. As a result, Indonesian language and literature have not yet become lessons that students enjoy. Literature teachers have not been able to use compelling methods. Many literary teachers lack sufficient interest and talent regarding literature. The impact of failure on students in developing, language skills, and positive attitudes towards Indonesian language and literature. Improving the quality of Indonesian education in the era of globalization must be comprehensive or comprehensive, emphasizing the implementation of the autonomy of education management, by creating various ways to achieve the objectives of national education as a whole and to immediately catch up with other countries. A tool to measure the success of a learning that is teachers who are innovative, creative and can choose the right learning points. Steps to become a creative teacher include (1) becoming an explorer of the mind, (2) developing questions (3) developing as many ideas as possible, and (4) creating an interesting and fun learning model